Increased Oral Care Needs and Third Molar Symptoms in Women with Gestational Diabetes Mellitus: A Finnish Gestational Diabetes Case-Control Study - Pukkila Jenni; Mustaniemi Sanna; Lingaiah Shilpa; Lappalainen Olli-Pekka; Kajantie Eero; Pouta Anneli; Kaaja Risto; Eriksson Johan G; Laivuori Hannele; Gissler Mika; Vääräsmäki Marja; Keikkala Elina (MDPI, 2022)
(1) Hyperglycemia and oral pathology accelerate each other in diabetes. We evaluated whether gestational diabetes mellitus (GDM) is associated with self-reported increased oral health care needs and oral symptoms, including third molar symptoms, during pregnancy. (2) Pregnant women with (n = 1030) and without GDM (n = 935) were recruited in this multicenter Finnish Gestational Diabetes study in 2009-2012. Of the women with GDM, 196 (19.0%) receiving pharmacological treatment, 797 (77.0%) receiving diet treatment and 233 (23.0%) with recurrent GDM were analyzed separately. Oral health was assessed using structured questionnaires and analyzed by multivariable logistic regression adjusted for background risk factors. (3) Women with GDM were more likely to report a higher need for oral care than controls (31.1% vs. 24.5%; odds ratio (OR) 1.39; 95% confidence interval (CI) 1.14-1.69), particularly women with recurrent GDM (38.1% vs. 24.5%; OR 1.90; 95% CI 1.40-2.58). Women with pharmacologically treated GDM (46.9%) more often had third molar symptoms than controls (36.1%; OR 1.57; 95% CI 1.15-2.15) than women with diet-treated GDM (38.0%; OR 1.47; 95% CI 1.07-2.02). (4) GDM is associated with perceived oral care needs. Third molar symptoms were associated with pharmacologically treated GDM.